Systemic Risk Contribution and Bank’s Competitiveness - buddi wibowo (STIE Malangkucecwara, 2022)
There are two competing views about bank’s competitiveness and its systemic risk contribution: competition-stability and competition-fragility. Previous research shows mixed results. To test empirically the relationship, this research proposes a quadratic functional form that may reconciliate these two opposite views. Using Marginal Expected Shortfall as individual bank’s systemic risk contribution measurement and Lerner Index as individual bank’s competitiveness, this research find that the relationship resembles U-shape. In the first phase, competition creates prudent banking operation and low systemic risk contribution. But when competition become excessive, competition drive dominant bank to be a systematically important financial institution which may cause a serious systemic defaults and threat financial system stability.